1981
DOI: 10.2105/ajph.71.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of N. meningitidis from patients in a gonorrhea screen program: a four-year survey in New York City.

Abstract: In the course of the screening program for gonorrhea in New York City, a total of 964 N. meningitidis strains were recovered from the genitourinary tract and/or anal canal over a four-year period (April 1975-April 1979, the rate of such recoveries having tripled during this time.The majority of strains were isolated from anal canal cultures of male patients most of whom were seen in a clinic treating homosexuals. N. meningitidis and N. gonorrhoeae were cultured together from 41 patients: in 24 cases from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Meningococci of clinical importance have been isolated from genitourinary sites (8,11). Furthermore, the occurrence of double infections with N. meningitidis and N. gonorrhoeae (8) increase the possibility that beta-lactamase-producing N. gonorrhoeae isolates may transfer their plasmids to the meningococcus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meningococci of clinical importance have been isolated from genitourinary sites (8,11). Furthermore, the occurrence of double infections with N. meningitidis and N. gonorrhoeae (8) increase the possibility that beta-lactamase-producing N. gonorrhoeae isolates may transfer their plasmids to the meningococcus.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the occurrence of double infections with N. meningitidis and N. gonorrhoeae (8) increase the possibility that beta-lactamase-producing N. gonorrhoeae isolates may transfer their plasmids to the meningococcus. Although N. meningitidis has generally been regarded as susceptible to penicillin, the characterization of plasmids in this species portends serious therapeutic complications.…”
Section: Methodsmentioning
confidence: 99%
“…Very high Nm carriage rates of over 40% have been reported in men who have sex with men (MSM) [9][10], and one study reported higher carriage rates in MSM (23.8%) than in heterosexual men (11.6%) [11]. Further known risk factors for meningococcal disease, such as exposure to tobacco smoke and crowding [12,13], may also be more prevalent in venues where MSM meet.…”
Section: Introductionmentioning
confidence: 99%
“…In certain groups, e.g. in adolescents, soldiers in barracks, men who have sex with men (MSM), markedly higher carriage rates of 20-40 % were reported [14][15][16][17][18][19][20]. Colonization with meningococci only rarely leads to invasive disease.…”
Section: Pathogenmentioning
confidence: 99%